Living As Citizen In Smart City - Lestari, Lara Ayu; Angreni, Dyah Kuntorini Dwi; Zana, Iqbal Saputra; Andreastuti, Desie; Bato, Bulan Erika; Perwitasari, Dyah Rahayuning (Journal of Education on Social Science (JESS), 2025)
The idea of smart cities has gained traction recently. It has attracted much attention from administrators, legislators, urban planners, and others in response to the complicated problems caused by unparalleled urbanization. However, public participation or citizen engagement is essential in the smart city concept to achieve the goals optimally. This research will primarily focus on several methodologically crafted problem sets to produce thorough analytical results. They ask how the notion of "smart cities" fits into the bigger picture of how citizen engagement in green cities affects Indonesia's green economy and ultimately, how well Indonesia's smart cities align with the 1945 Constitution. This study looks at smart city-based policies from the perspectives of participation, economy, and constitution, which is different from previous studies. The findings indicate that several smart city programs and regulations still rely on local government policies, which means that residents' rights are not allocated fairly. The construct is significant in developing ecologically sound entrepreneurship through initiatives to promote interest in community participation through green entrepreneurship orientation. The smart city concept is a means of achieving the success of community engagement in promoting a green economy and constitution.